Takeover Bidding with Signaling Incentives - Liu, Tingjun (Review of Financial Studies, 2012)
[This study examines takeover bidding contests in which privately informed bidders have incentives to signal high values to uninformed investors through their bids. Such incentives could arise in a large number of situations from financing and managerial concerns. The findings show that the dynamic nature of the takeover contests plays a critical role in the signaling process, allowing bidders to signal high values in two ways. Such signaling bears important consequences on the bids, the allocative efficiency, the target's and bidders' profits, as well as the winner's post-takeover stock price performance and volatility.]